Exposed - Scottoline, Lisa (Scottoline, Lisa. Rosato & DiNunzio novel., 2017)
"Plot twists aplenty raise the stakes." --People Magazine A BATTLE FOR JUSTICE PITS PARTNER AGAINST PARTNER... Mary DiNunzio wants to represent her old friend Simon Pensiera, a sales rep who was wrongly fired by his company, but her partner Bennie Rosato represents the parent company. When she confronts Mary, explaining this is a conflict of interest, an epic battle of wills and legal strategy between the two ensues--ripping the law firm apart, forcing everyone to take sides and turning friend against friend. SOMETIMES LOYALTY CAN BE LETHAL"--